Influence of Complex E-commerce Network Setting on National Sports in China - Wang Yongping (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
Sports is promoted in China through e-commerce applications in all age groups, particularly among the retied and people with disability. E-commerce thus plays the educational role in developing awareness about sports. Physical fitness is also promoted through such e-commerce activities and makes a significant educational effect on the whole society. Physical health programs have become an integral part of public awareness education making them a common habit. However, China still lacks relevant theoretical research, especially in e-commerce systems based on complex networks. This paper analyzed e-commerce network settings and complex system frameworks based on the complexity networks. In the light of these analyses, national sports' status quo was summarized, and the significance of developing national sports was emphasized. The study used literature survey, comparative research, questionnaire survey, mathematical statistics, and logic analysis methods, and used several types of classifications of the sample of the study, namely the retired workers, the disabled, and the underdeveloped regions in Northwest China. According to statistics, the results show that the establishment of e-commerce outlets based on complex networks had a positive effect on retired employees as it increased their awareness and participation in sports. E-commerce, in spite of all its complexities, has thus provided a convenient online fitness platform for retired employees, disabled people, and people in the backward regions. Simultaneously, various e-commerce websites and mobile Apps have has also played an active role to promote sports activities among these sections of society. The study concluded that an e-commerce network setting based on complex networks could promote sports in China and ultimately affect people's health and fitness.